Digital Communication Ethics Among Students at MTsN Kota Bogor A Review of the Value of Hifzhu Al-Lisan - Muawwanah, Siti Sa'diatul; Basith, Yudril (Qawwam : The Leader's Writing, 2026)
This study aims to analyze students' digital communication ethics practices at MTs N Kota Bogor by examining the value of hifzhu al-lisan as a form of moral control in digital communication. The study employs a descriptive qualitative approach, utilizing data collection techniques such as in-depth interviews, participant observation, and documentation. Research informants were selected using purposive sampling, involving students in grades VII, VIII, and IX, as well as teachers of Akidah Akhlak, Civic Education, and ICT. Data analysis was conducted using the stages of open coding, axial coding, and selective coding. The research findings indicate that students' digital communication practices fall into two main categories: positive communication practices—such as the use of polite language, self-control, and social support—and negative communication practices—including the use of coarse language, cyberbullying, digital provocation, the dissemination of unverified information, and impulsive emotional expression. The findings also reveal a gap between students' understanding of digital communication ethics and their actual practices on social media. From the perspective of Hifzhu al-lisan, digital communication is not merely the act of conveying messages but also a moral responsibility to safeguard language, emotions, and information. Therefore, the internalization of hifzhu al-lisan values through education, the cultivation of school culture, and the strengthening of digital literacy are crucial in shaping students' digital communication character to be more polite, reflective, and responsible in the digital age.